@myTabu—A Placebo Controlled Randomized Trial of a Guided Web-Based Intervention for Individuals Who Sexually Abused Children and Individuals Who Consumed Child Sexual Exploitation Material: A Clinical Study Protocol - Fromberger, Peter; Schröder, Sonja; Bauer, Louisa; Siegel, Bruno; Tozdan, Safiye; Briken, Peer; Buntrock, Claudia; Etzler, Sonja; Rettenberger, Martin; Leha, Andreas; Müller, Jürgen L. (Frontiers in Psychiatry, 2021)
Background. There is a high demand for evidence-based and cost-effective treatment concepts for convicted individuals who sexually abused children (ISAC) and individuals who consumed child sexual exploitation material (ICCSEM) under community supervision (CS). The @myTabu-consortium developed a guided web-based intervention for convicted ISAC and ICCSEM under CS consisting of six online modules targeting psychological meaningful risk factors. The study aims to evaluate the effectiveness of this guided web-based intervention in reducing dynamic risk factors and the risk to re-offend compared to a placebo condition. Furthermore, these dynamic risk factors are measured before and after every module to evaluate their individual effectiveness to reduce the respective risk factor as well as risk to re-offend. This clinical trial protocol describes the planned methods as well as the intervention concept. Methods. The methodological design is a placebo controlled randomized add-on trial (N = 582) with follow-ups at 13 points in time. The placebo condition controls for attention and expectation effects and comprises the same amount of modules with a comparable temporal effort as the experimental intervention. The trial is conducted as an add-on to community supervision as usually done. Primary outcomes are dynamic risk factors assessed by self-report risk assessment tools and officially recorded re-offenses. Discussion. To the best of our knowledge, the study is the first to compare the (cost-) effectiveness of a guided web-based intervention for convicted ISAC and ICCSEM under community supervision against a placebo condition. Methodological limitations (e.g., potential ceiling- or volunteers-effects) are discussed. Trial registration. German Clinical Trial Register (DRKS 00021256). Prospectively registered: 24.04.2020.